Peran Iman Kristen sebagai Upaya Mengatasi Depresi - Dupe, Selvy Iriany Susanti; Manang, Yakobus Maramba; Anapaki, Maria Jera; Aji, Anggreni Pengu (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This study aims to explain the role of Christian faith in overcoming depression. The method used is a qualitative method with a literature study approach. The results of the study state that Christian faith plays a role in efforts to overcome depression. If a person has a good Christian faith, then it is expected that the person can strive to overcome depression. Furthermore, if a person has a poor Christian faith, then efforts to overcome depression will be disrupted / hampered, and may not even be pursued. Suggestions for individuals that every person, especially Christians should realize that everyone can be affected by depression. For every family, it is necessary to be aware and sensitive to mental illnesses, one of which is depression. Each individual does not feel alone in facing problems, but knows that there is a family that is always ready to support. The church is one of the best shields that can be a protector for individuals in facing various life challenges, so as to avoid depression.